Indications for flexible fiberoptic bronchoscopy and its safety in the very elderly - R. D’Ippolito; A. Foresi; C. Castagnetti; S. Gesualdi; A. Castagnaro; E. Marangio; D. Olivieri (Monaldi Archives for Chest Disease, 2016)
Aim. To evaluate the indications and the safety of fiberoptic bronchoscopy (FOB) with bronchoalveolar lavage (BAL), protected specimen brushing (PSB), endobronchial biopsy (EBB), and transbronchial biopsy (TBB) in a population of very elderly patients. Methods. We performed a retrospective study of all adult patients, aged 50 years or older, who underwent FOB in the Bronchology Unit of the University of Parma Hospital between 1 January, 2003 and 31 April, 2005. Bronchoscopy records of 436 consecutive patients, including 191 patients, 75 yrs of age and older (“very elderly”; =>75 yrs), were reviewed. Results. Patients aged 75 years were no different with regard to gender, BMI, baseline FEV1/FVC ratio, baseline SaO2, and blood pressure. The primary indication in patients aged <75 years, was to assist in the diagnosis of a pulmonary mass of unknown aetiology (33%) and to remove secretions in the very elderly patients (31%). Indications for FOB and sampling procedures in the two groups were similar. Approximately 30% of patients in each group required supplemental oxygen during the procedure and fever occurred in 9.2% and 10.3% of patients, respectively.Hypertension and bleeding were relatively rare and did not occur more often in the very elderly. Conclusions. Indication for FOB did not vary with age and adverse events in both groups were uncommon and generally not severe.